Response of Soil CO2 Emission and Summer Maize Yield to Plant Density and Straw Mulching in the North China Plain. (23rd July 2014) - Liu, Quanru; Liu, Xinhui; Bian, Chengyue; Ma, Changjian; Lang, Kun; Han, Huifang; Li, Quanqi
Abstract : Demand for food security and the current global warming situation make high and strict demands on the North China Plain for both food production and the inhibition of agricultural carbon emissions. To explore the most effective way to decrease soil CO2 emissions and maintain high grain yield, studies were conducted during the 2012 and 2013 summer maize growing seasons to assess the effects of wheat straw mulching on the soil CO2 emissions and grain yield of summer maize by adding 0 and 0.6 kg m −2 to fields with plant densities of 100 000, 75 000, and 55 000 plants ha −1 . The study indicated that straw mulching had some positive effects on summer maize grain yield by improving the 1000-kernel weight. Meanwhile, straw mulching effectively controlled the soil respiration rate and cumulative CO2 emission flux, particularly in fields planted at a density of 75 000 plants ha −1, which achieved maximum grain yield and minimum carbon emission per unit yield. In addition, soil microbial biomass and microbial activity were significantly higher in mulching treatments than in nonmulching treatments. Consequently, summer maize with straw mulching at 75 000 plants ha −1 is an environmentally friendly option in the North China Plain.